Response of finger millet under organic nutrient management in sodic soil - Rathika, S; Vinoth, R; Kokilavani, S; Dinesh, G K; Jagadeesan, R; Ayyadurai , P; Satheeshkumar, N; Venkatalakshmi, K; Selvarani, A; Baskar, M; Vinodhini, S M; Janaki, P; et al. (Plant Science Today, 2025)
Finger millet is a traditional food crop that holds immense significance due to its versatility, climate resilience, and higher nutritional value. Finger millet growers face challenges due to poor soil properties and environmental conditions. To meet the growing demand, finger millet production must be substantially increased through suitable organic nutrient management practices. Hence, the present study was carried out to evaluate the effect of organic nutrient management on the productivity and profitability of finger millet. Field experiments were conducted during the Kharif seasons of 2019 and 2020 at Anbil Dharmalingam Agricultural College and Research Institute, Tiruchirappalli in a randomized block design with three replications. The treatments comprised of 100 and 125% N equivalent either through farmyard manure (FYM) or vermicompost or composted poultry manure, 50% N equivalent FYM + 50% N equivalent vermicompost, 50% N equivalent FYM + 50% N equivalent composted poultry manure, 50% N equivalent vermicompost + 50% N equivalent composted poultry manure and 100% recommended dose of fertilizer (RDF) (60: 30: 30 kg NPK/ha) + FYM (12.5 t/ha). Finger millet variety TRY 1 was used as test crop. The results revealed that the application of 100% RDF (60: 30: 30 kg NPK/ha) + FYM (12.5 t/ha) registered significantly higher growth, yield attributes and yield of finger millet than other treatments. However, it was comparable with 125% N equivalent vermicompost (3.8 t/ha) and 125% N equivalent composted poultry manure (3.5 t/ha). With regard to economics, application of 125% N equivalent composted poultry manure (3.5 t/ha) registered higher net return (Rs.41621/ha) and benefit cost ratio (BCR) (2.28) over other treatments. Hence, application of 125% N equivalent vermicompost (3.8 t/ha) or 125% N equivalent composted poultry manure (3.5 t/ha) could be recommended as organic nutrient management strategy for getting higher productivity and profitability of irrigated finger millet under sodic soil.